Implementasi Undang-Undang no. 32 tahun 2009 tentang Lingkungan Hidup dalam Tanggung Jawab dan Kewajiban di PT Djarum OASIS - Brian (Universitas Wahid Hasyim, 2025)
This study aims to analyze the implementation of Law No. 32 of 2009 concerning Environmental Protection and Management, especially related to the management and control of liquid waste at PT Djarum OASIS. This research method uses a normative juridical method that relies on secondary data, such as laws and regulations, scientific journals, and relevant law books. Data collection techniques are also carried out through observation and documentation. The results of this study show that PT Djarum Oasis has fulfilled the obligations stipulated in Law No. 32 of 2009, including in the management of liquid waste, and has successfully obtained the Blue PROPER award from the Ministry of Environment and Forestry of the Republic of Indonesia as a form of recognition for the company's performance in preserving the environment.